Epioptics - 7 : (World Scientific, 2004)
This book assesses the capabilities of state-of-the-art optical techniques in elucidating the fundamental electronic and structural properties of semiconductor and metal surfaces, interfaces, thin layers, and layer structures. It also examines the usefulness of these techniques for optimization of high quality multilayer samples through feedback control during materials growth and processing. Emphasis is given to dynamical processes through the use of pump–probe techniques, together with the search for new optical sources. Some new applications of scanning probe microscopy to materials science and biological samples (dried and in vivo) with the use of different laser sources are also presented.